Geographical inquiry analysis of critical thinking ability, learning achievement and self-efficacy - Lasaiba, Mohammad Amin; Arfa, Arman Man (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
Inquiry learning is an effective method in training students to develop knowledge, skills, and practices. This study aims to examine the effectiveness of inquiry learning method in the context of geography lessons, especially in relation to critical thinking skills, learning achievement, and student self-efficacy. This study used a quasi-experimental design with a population of grade X students at SMA Negeri 1 Leihitu, and the class sample was selected through purposive sampling technique. The research instruments consisted of tests to measure learning achievement and critical thinking skills, and questionnaires to assess self-efficacy. The data obtained were analyzed using the Multivariate Analysis of Variance (MANOVA) test. The results showed that there were significant differences in critical thinking skills, learning achievement, and self-efficacy of students after applying the geography inquiry learning method, with a significance value of t less than 0.05, so the null hypothesis (ð»0) was rejected. In conclusion, the geography inquiry learning method is proven to be effective and practical to be applied in learning in high school.